Systematic Literature Review: The Role of Compensation in Enhancing Performance Outcomes - Hanief Kurniawan (ITB AAS Indonesia Surakarta, 2025)
This systematic literature review (SLR) examines how compensation strategies both monetary (e.g. salary, bonuses, pay-for-performance) and non-monetary (e.g. recognition, benefits, flexibility) affect employee performance at the individual, team, and organizational levels. Following the PRISMA 2020 guidelines, empirical studies (2014–2024) on compensation and performance were searched from the Scopus and Web of Science databases. After screening and quality appraisal (using the Joanna Briggs Institute tools), 67 primary research articles met the inclusion criteria. The findings were synthesized, highlighting that monetary incentives generally exhibit a positive, yet context-dependent, effect on performance, while non-monetary rewards often enhance intrinsic motivation and engagement. Several studies identified mediating factors such as motivation, justice perceptions, and job satisfaction, which explain how compensation influences performance. Moreover, moderators such as organizational culture, ownership structure, and leadership style shape the strength of these effects. In conclusion, both forms of compensation can improve performance when aligned with organizational context and employee needs. Gaps were identified, including limited evidence on long-term outcomes and under-researched non-monetary incentives. A research agenda is proposed to explore optimal compensation designs and their interactions with work motivation and team dynamics.